Study some virulence factors of Escherichia coli isolates (Journal of the College of Basic Education, 2022)
Some Factors determining the virulence of Escherichia coli ( E. coli ) isolates were studied ,of 25 isolates , 17(group A) uropathogenic E. coli ,6 (group B) infected gastrointestinal tract , 2 (group C) infected wound , beside these group we use the standard strain E. coli HB101 as control group.The twenty five isolates were tested for adherence capability to human buccal cavity epithelial cells by in vitro experiment .